Occurrence and Risk Factors of Adverse Drug Reactions in Patients Receiving Bivalirudin as Anticoagulant During Percutaneous Coronary Intervention: A Prospective, Multi-Center, Intensive Monitoring Study - Ping Li; Hongyan Zhang; Caidong Luo; Zheng Ji; Zeqi Zheng; Zhenyong Li; Fan Wu; Jinlong Li; Lang Hong (Frontiers in Cardiovascular Medicine, 2022)
BackgroundBivalirudin is a common anticoagulant during percutaneous coronary intervention (PCI); however, since its application in China, it still lacks comprehensive evaluation of adverse events (AEs) or adverse drug reactions (ADRs) under the real-clinical setting conditions with a large-sample-size population. Therefore, this prospective, multi-center, intensive monitoring study aimed to comprehensively investigate the occurrence and risk factors of AEs and ADRs during PCI with bivalirudin as an anticoagulant.MethodsA total of 3,049 patients who underwent PCI with bivalirudin as anticoagulant from 27 Chinese medical centers were enrolled. Safety data (AEs/ADRs) were collected from hospital admission to 72 h after bivalirudin administration; then, patients were followed up at the 30th day with the safety data collected as well.ResultsA total of 414 (13.58%) patients occurred AEs, among which 31 (1.02%) cases suffered from severe AEs and 8 (0.26%) cases died due to AEs. Importantly, 118 (3.87%) patients occurred bivalirudin related ADRs, among which 7 (0.23%) cases suffered from severe ADRs while no case (0%) died due to ADRs. Of note, 7 (0.23%) patients showed new ADRs, 34 (1.12%) patients experienced bleeding, and 79 (2.59%) patients had thrombocytopenia. Furthermore, age, renal function impairment, CRUSADE high risk stratification independently correlated with total ADRs risk; CRUSADE high risk stratification, emergency operation, full dose bivalirudin independently associated with bleeding risk; age, renal function impairment independently related to thrombocytopenia risk.ConclusionBivalirudin is well-tolerated as an anticoagulant for PCI procedure; meanwhile, older age, renal function impairment, and CRUSADE high risk stratification serve as independent risk factors of bivalirudin related ADRs.